Environmental justice, conservation, and the politics of pipelines - Lester, Julie A., author (Colorado State University. Libraries, 2017)
The United States Federal Energy Regulatory Commission recently approved the construction of a natural gas pipeline through three southern states. Supporters of the pipeline focused on the economic benefits that pipeline construction would bring to communities, while those in opposition questioned the environmental justice and ecological impact of pipeline construction. This paper will explore the politics of the approval and construction process for the pipeline with a focus on the narratives of public and private actors in support of and in opposition to the pipeline. Through an analysis of narratives presented in the media, public hearings, and other sources, interested parties may learn more about how stakeholders highlighted issues related to economics, environmental justice, and conservation to advance their agenda.
Presented at the Environmental justice in the Anthropocene symposium held on April 24-25, 2017 at the Lory Student Center, Colorado State University, Fort Collins Colorado. This symposium aims to bring together academics (faculty and graduate students), independent researchers, community and movement activists, and regulatory and policy practitioners from across disciplines, research areas, perspectives, and different countries. Our overarching goal is to build on several decades of EJ research and practice to address the seemingly intractable environmental and ecological problems of this unfolding era. How can we explore EJ amongst humans and between nature and humans, within and across generations, in an age when humans dominate the landscape? How can we better understand collective human dominance without obscuring continuing power differentials and inequities within and between human societies? What institutional and governance innovations can we adopt to address existing challenges and to promote just transitions and futures?
Keywords: Dakota Access Pipeline; Sabal Trail Pipeline; pipelines; natural resources; conservation